The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ina.12709
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure and health risks of volatile organic compounds of hotel housekeepers: Field measurements of exposure and health risks

Abstract: Hotel housekeepers represent a large, low‐income, predominantly minority, and high‐risk workforce. Little is known about their exposure to chemicals, including volatile organic compounds (VOCs). This study evaluates VOC exposures of housekeepers, sources and factors affecting VOC levels, and provides preliminary estimates of VOC‐related health risks. We utilized indoor and personal sampling at two hotels, assessed ventilation, and characterized the VOC composition of cleaning agents. Personal sampling of hotel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…Exposed to harmful chemicals, such as ammonia and solvents in cleaning products, hotel housekeepers suffer from prolonged contact with these chemical agents, which often intensify dermatitis, respiratory diseases and other health conditions (Hsieh et al, 2016;Lin et al, 2020). Employees who work with cleaning chemicals are also susceptible to allergic reactions and skin rashes from long and constant use of latex gloves (Kline et al, 2014).…”
Section: Ijchm 3310mentioning
confidence: 99%
“…Exposed to harmful chemicals, such as ammonia and solvents in cleaning products, hotel housekeepers suffer from prolonged contact with these chemical agents, which often intensify dermatitis, respiratory diseases and other health conditions (Hsieh et al, 2016;Lin et al, 2020). Employees who work with cleaning chemicals are also susceptible to allergic reactions and skin rashes from long and constant use of latex gloves (Kline et al, 2014).…”
Section: Ijchm 3310mentioning
confidence: 99%
“…Egypt is one of the first countries to adopt proactive measures to cope COVID-19. As such, the Egyptian Ministry of Tourism and Antiquities (EMTA) launched a consciousness campaign titled "Stay at home, be safe," in solidarity with World Health Organization guidelines on the novel virus hazards to physical health (Lin et al, 2021). Otherwise, the gravity of this pandemic reached the Egyptian hotel industry and led to a substantial share of the economic losses in this massive industry (Gössling et al, 2020).…”
Section: Negative Repercussions Of Covid-19 On the Hotel Industrymentioning
confidence: 99%
“…Furthermore, the need for wellventilated insulation rooms is greater for suspects (WHO, 2020b). Furthermore, after sneezing, throw used tissues into ‫والفنادق‬ ‫السياحة‬ ‫كلية‬ ‫مجلة‬ -‫عدد‬ 01 -‫ديسمبر‬ 0100 sealed bins and ensure ventilation of various corridors as preventive measures (Belingheri et al, 2020;Lin et al, 2021). Zhang et al ( 2020) stressed the necessity of wearing leather gloves to reduce the chances of the virus staying on the surface of the hands, not only for food-handlers but also for all hotel employees.…”
Section: Occupational Health Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the conditions at which the consumer spray products are used, this simplifying assumption often fails to predict the exposure concentration [ 13 ]. For example, a study on hotel housekeepers attached with personal samplers reported nearly double the amount of VOC exposure compared to that calculated based on the concentration of the room assuming complex mixing [ 14 ]. This deviation could be explained by the heterogeneity of the ambient concentration during the use of consumer products.…”
Section: Introductionmentioning
confidence: 99%